AB0534 DEVELOPMENT OF A MULTI-MODALITY IMAGING APPROACH TO EVALUATE LUPUS NEPHRITIS AND INITIAL RESULTS. (June 2019) - Karp, David R.; Rovin, Brad H.; Boesen, Mikael; Kubassova, Olga; Lipsky, Peter
Abstract : Background: Lupus nephritis (LN) remains a significant cause of morbidity and mortality in subjects with Systemic Lupus Erythematosus (SLE). The gold standard for evaluation of LN remains the kidney biopsy, whereas renal function is usually evaluated by eGFR and urinary protein:creatinine ratio. More effective and sensitive methodology is needed to assess LN and also the response to treatment. Functional imaging of the kidney using quantitative techniques has great potential, as it can assess kidney function and pathologic changes non-invasively by evaluating perfusion, oxygenation, cellular density and fibrosis. Objectives: To develop a multi-modality imaging approach for the evaluation of the spectrum of pathologic changes in LN. Methods: In this multi-center study, subjects who were having a standard of care renal biopsy for LN were asked to participate in the imaging evaluation. Local Institutional Review Board approval was obtained, and subjects signed an Informed Consent Form. Dynamic contrast enhanced MRI (DCE-MRI) was employed to detect changes in vascularization and perfusion 1, Diffusion Weighted Imaging (DWI) to assess interstitial diffusion, T2*Map/BOLD - the tissue oxygenation and T1rho to evaluate fibrosis 2 . The imaging scores will be compared to renal biopsy, including ISN/RPS classification of LN, activity index and chronicity index. Results: Five patients have been evaluated to date and their imaging data assessed for quality. The initial results have demonstrated the feasibility of acquiring multi-modality imaging data, including dynamic imaging sequences, in the multi-center trial setting. Figure 1 illustrates scans from a representative patient. This study will determine whether multi-modality imaging could become an effective, non-invasive tool to assess renal function and pathology in LN. Conclusion: The initial assessment of 5 LN subjects has established the feasibility of multi-modality imaging as a tool to evaluate LN in a multi-center study. By assessing functional and structural MRI outcomes and correlating them to clinical data, this study will provide essential preliminary evidence on the value of multi-modality imaging in diagnosis and evaluating the response to treatment of LN patients. References: [1] Rappachi S, et al. Magnetic Resonance Imaging, 2015 Nov;33(9):1066-1074. [2] Boesen M, et al. PET Clin. 2018 Oct;13(4):523-550. Disclosure of Interests: David R Karp: None declared, Brad H Rovin: None declared, Mikael Boesen Shareholder of: Image Analysis Group, UK, Grant/research support from: Image Analysis Group, UK, OAK Foundation, EUROSTAR, Consultant for: Esaote, Eli Lilly, Celgene, Carestream, UCB, Abbvie, Pfizer, Astra Zeneka, Roche, Siemens, Image Analysis Group, Olga Kubassova Shareholder of: IAG, Image Analysis Group, Employee of: IAG, Image Analysis Group, Peter Lipsky Consultant for: Consulting fees from Horizon Pharma